ETIOPATOGENESIS OF OSTEODYSTROPHY OF ZAANENSKA BREED OF GOATS - Маслак, Ю. В.; Собакар, А. В. (Scientific Progress & Innovations, 2015)
It is established that alimentary osteodystrophy of goats of dairy breeds is characterized both clinical signs, and specific by dynes, which biochemical indicators display both changes of the general metabolic status of animals and a condition of connecting tissue, in particular, of the bone. This maintenance of glycoproteins, communities of the hondroitinsulfat separate glikozaminoglikan, activity of alkaline phosphatase and its bone isoenzyme, activity of sour phosphatase, the general and ionized calcium and phosphorus in serum of animals’ blood.